Habituation of Fasting and Mosque Prayers: Family Educational Efforts to Cultivate Worship Independence in Early Childhood - Kasmila, Amia; Rizqi, Diah Irdiyana; Erlina, Erlina; Ghazi, Fachrul; Kholid, Idham (Ahlussunnah: Journal of Islamic Education, 2025)
The phenomenon of declining interest among children in religious activities indicates the need for more practical and continuous family education in instilling religious values. The family plays a primary and essential role in shaping the spiritual foundation of children through habit formation and role modeling. This study aims to explore family-based Islamic education strategies in fostering independence in worship among young children through prayer and fasting activities. This study uses a qualitative method with a library research approach, namely by reviewing and analyzing various scientific sources such as accredited journals, books, and the latest research results (2021–2025) relevant to the theme of worship habits in Muslim families. Data analysis was conducted using content analysis techniques with stages of reduction, theme categorization, and conclusion drawing oriented towards theoretical findings and Islamic education practices in the family. The results of the study show that effective religious habits for children can be built through three main aspects: parental role modeling, consistent worship routines, and strengthening the religious environment at home. In addition, the targeted use of digital media and positive communication within the family also strengthen children's spiritual motivation. This study produced the concept of the Islamic Family Worship Habituation Model as a practical strategy for fostering spiritual independence in early childhood. The implications of the study emphasize the importance of synergy between families, Islamic educational institutions, and the social environment in shaping a generation of Muslims who are independent, have strong character, and are rooted in the values of faith and piety.